Return to Work After Surgery for Cervical Radiculopathy: A Nationwide Registry-based Observational Study. Issue 4 (15th February 2023) - Hara, Sozaburo; Lønne, Vetle V.; Aasdahl, Lene; Salvesen, Øyvind; Solberg, Tore; Gulati, Sasha; Hara, Karen W.
Abstract : Study Design: An observational multicenter study. Summary of Background Data: Return to work (RTW) is increasingly used to assess the standard, benefit, and quality of health care. Objective: The aim of this study was to evaluate sick leave patterns among patients undergoing surgery for cervical radiculopathy and identify predictors of successful RTW using two nationwide databases. Materials and Methods: Data from the Norwegian Registry for Spine Surgery (NORspine) and the Norwegian Labour and Welfare Administration were linked on an individual level. We included patients between 18 and 60 years of age registered in NORspine from June 2012 through December 2019 that were temporarily out of the labor force for medical reasons at the time of surgery. We assessed types and grades of sickness benefits before and after surgery and conducted logistic regression analyses. Results: Among 3387 patients included in the study, 851 (25.1%) received temporary benefits one year before surgery. The proportion of recipients increased steadily towards surgery. Postoperatively the medical benefit payment decreased rapidly, and half of the patients had already returned to work by four months. The rate of RTW reached a plateau at one year. By the end of the third year, 2429 patients (71.7%) had returned to work. The number of sick days, categorized as 90 or less, during the year before surgery had the most powerful association with RTW at two years (odds ratio: 4.54, 95% CI: 3.42–6.03, P <0.001). Improvement in neck-related disability was the second strongest predictor (odds ratio: 2.17, 95% CI: 1.69–2.78, P <0.001). Conclusion: RTW after cervical radiculopathy surgery occurs primarily during the first year. The strongest predictor of RTW was fewer sick days before surgery. The clinical improvement after surgery had a lesser impact. Level of Evidence: 2.